La visita de Guaqui (1594) y los antropónimos de la lengua puquina entre los pescadores y agricultores uros de la cuenca del lago Titicaca - Pärssinen, Heli (2024)
During the early colonial period, Puquina was one of the three common languages used in the Lake Titicaca basin, along with Aimara and Quechua. In this article, we examine the anthroponyms of the Puquina language in the unpublished Visita of Guaqui (1594), which lists 1000 tributary men by their surnames, that were in fact their former names. It appears that most of the adult male Uros on the visita list were fishermen and farmers, and the Serranos were mostly herders and farmers. The Uros originally spoke Puquina and Uro. Our analysis of the Uro tributaries - based on colonial sources as well as archaeological and linguistic studies - indirectly supports Cerrón-Palomino’s hypothesis that the so-called secret language of the Incas may have been Puquina, and especially that the vocabulary of Puquina may have influenced Cuzco Quechua. In addition, the results show some correspondence between anthroponyms and toponyms, and in general they support the hypothesis that one of the general languages of the ancient Tiwanaku state may have been Puquina.